Building Bridges between Catholicism and Socialism: Ernst-Wolfgang Böckenförde and the Social Democratic Party of Germany. (May 2020) - Ruff, Mark Edward
Abstract: This article examines the ideological and political transformations that allowed dialogue between Catholics and socialists to bear fruit in the Federal Republic of Germany in the immediate post-war era. It focuses on the role played by Ernst-Wolfgang Böckenförde, the prominent Catholic intellectual, constitutional theorist, historian and future Constitutional Court justice.